The effectiveness of acupressure using aromatherapy to reduce dysmenorrhea pain at teenager student - Husnul Khotimah; Sri Utami Subagio (Universitas 'Aisyiyah Yogyakarta, 2022)
One of the complaints during menstruation is dysmenorrhea. As many as 90% of adolescent girls worldwide experience menstrual problems and more than 50% of menstruating women experience primary dysmenorrhea. Another way of healing to reduce the symptoms of dysmenorrhea in addition to pharmacological therapy is by giving acupressure and aromatherapy. This research method is Quasi Experimental Design with Nonequivalent Control Group Design, 60 sample. The treatment group was given acupressure therapy using lemon essential oil aromatherapy at points LI 11, LI 4, dan ST 36 on day 1-2 menstruation, the control group was given acupressure therapy without using aromatherapy. Then do the post test. The results of statistical analysis using Mann Whitney revealed that the p value: 0.000 is smaller than ( 0.05), it can be concluded that there is an effect of acupressure using aromatherapy on dysmenorrhea. Acupressure using aromatherapy is effective to treat dysmenorrhea in adolescents. The results of this study are expected to be one of the methods that can be used in the practice of midwifery services. It is hoped that further researchers will carry out other non-pharmacological treatments to overcome dysmenorrhea